PERAN HIPOALBUMINEMIA TERHADAP KEJADIAN PNEUMONIA PADA PASIEN STROKE FASE AKUT - INDRADEWI K, A.A.Ayu Suryapraba ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Pneumonia is one of the most common nosocomial infection in stroke patients that lengthening hospitalization and associated with morbidity and mortality in patients with stroke. Hypoalbuminemia is known to be associated with increasing risk of infection. The aim of this study was to examine the role of hypoalbuminemia on pneumonia events in patiens with acute phase stroke. This study using case control design, by restrospectively analysing the medical records of patients with acute phase stroke in Stroke Unit and Neurology Ward RSUP Dr. Sardjito Yogyakarta. Subjects with Hospital Acquired Pneumonia (HAP) were categorized as case group and those without HAP were categorized as control group. Reference value of serum albumin level used was between 3,5-5,0 g/dL, degree or neurological deficit was measured with Skala Stroke Gadjah Mada (SSGM), and dysphagia was assesed with Acute Stroke Dysphagia Screening (ASDS). A total of 54 subjects were included in this study, with 27 subjects in each group. Hypoalbuminemia was found in 23 subjects (42,6%) from whole samples, and in 16 subjects (59,3%) with pneumonia. Hypoalbuminemia is a risk factor of pneumonia events in patients with acute phase stroke (OR: 4,15; 95%CI: 1,31-13,16; p=0,013). Other risk factors of pneumonia are severe neurological deficit, leukocytosis, dysphagia and use of NGT. Hypoalbuminemia is risk factor of pneumonia in patients with acute phase stroke in this study, but not an independent risk factor. Severe neurological deficit, leukocytosis, dysphagia and use of NGT were found as confounding factors to role of hypoalbuminemia on pneumonia in patients with acute phase stroke.